Banks as Supply Chain Risk Managers: A Management-Oriented Review - Liu, Siyu (Exploring Science Academic Conference Series, 2026)
This paper explores the importance of banks in defining supply chain risk at a management and system-level. Although the existing literature has mainly concentrated on the efficiency of the supply chain and financial intermediation, little has been done on the role of banks in shaping risk dynamics in interrelated production networks. This gap is filled in this paper through the conceptualization of banks as active participants in supply chains and not as passive providers of capital. Based on the literature on banking, supply chain management, and organizational theory, the study determines three important mechanisms by which banks affect supply chain risk: financial, informational, and governance mechanisms. These processes influence the way liquidity is distributed, the transmission of risks, and responses of firms to uncertainty in supply networks. The results indicate the duality of banks as stabilizers and amplifiers of supply chain risk. In normal circumstances, banks make the banking system resilient through liquidity provision and coordination of the firms. Banks can however limit credit during times of financial strain, causing liquidity crises and ripple effects throughout supply chains. In general, the research adds to the literature by uniting the financial and management viewpoints and highlighting the significance of a system-level approach to the concept of supply chain risk.